THE MINIATURE OF SOLAR SYSTEM MEDIA IN IMPROVING SCIENCE UNDERSTANDING AND LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Ahmad Jumran; Framz Hardiansyah; Ahmad Shiddiq (El Midad, 2025)
Science learning in elementary schools often faces difficulties in teaching abstract concepts, such as the solar system, which are difficult for students to understand. Interactive and visual learning media, such as miniature solar system media, can solve this problem. This study aims to test the effectiveness of miniature solar system media in improving the understanding and learning outcomes of 5th-grade elementary school students. This study used a quasi-experimental design with two groups, experimental (using miniature media) and control (traditional learning methods), consisting of 25 students. Data were collected through a learning outcome test containing 25 questions about basic competencies. Data analysis was carried out using normality tests, homogeneity tests, regression tests, and hypothesis tests. The study showed that the miniature solar system media significantly improved students' science learning outcomes, with a t-test value of 7.334, and H1 was accepted. This study concludes that miniature media effectively enhances the understanding of abstract science concepts and can be implemented in science learning in elementary schools. The practical implications are the importance of teacher training to utilize this media optimally and the expansion of technology in science learning in elementary schools.